Strukturelle forhold kan være med til at nuancere forståelsen af velfærdsprofessionelles problematikker - Andersen, Peter Østergaard (Tidsskrift for Professionsstudier, 2024)
In recent decades, late modernity has developed in the direction of ever greater inclusion of affective relationships. This has implications for the welfare professions’ working conditions and the content of the work. The article illustrates how theories about the development of the ‘society as a whole’ can qualify our understanding of some of the problems that currently characterize the welfare professions.